Cortical Stimulation for brain mapping and seizure stimulation, pediatric practices throughout Canada: A national survey and systematic literature review - Maltseva, Margarita; Appendino, Juan Pablo; Cabounova, Pavlina; Andrade, Andrea; Kregel, Michelle; Hadjinicolaou, Aris; Weil, Alexander G; Jain, Puneet; Donner, Elizabeth; Borlot, Felippe; Dufresne, David; Huh, Linda; et al. (Neurophysiologie clinique, 2025)
INTRODUCTION: Diagnostic cortical stimulation (CS) in intracranial electroencephalography (iEEG) is an established epilepsy presurgical assessment tool to delineate relevant brain functions and elicit habitual epileptic seizures. Currently, no consensus exists as to whether CS should be routinely performed in pediatric patients. A significant challenge is their limited ability to cooperate during the procedure or to describe non-observable seizure semiology features. Our goal was to identify the spectrum of CS practices in Canada, for both eloquent cortex mapping and seizure stimulation. METHODS: An online survey, answered by all 8 Canadian pediatric epilepsy centers, enquired about implantation, stimulation methods, and use of standardized protocols. A systematic literature review extracted detailed stimulation parameters. RESULTS: Most of the institutions (n = 7/8) reported performing CS during presurgical evaluation. Four institutions indicated they perform stimulation in all implanted patients for the purpose of eloquent cortex mapping and seizure stimulation. The majority of physicians had their individual approach to CS. A largely variable approach to CS, mainly in the choice of stimulation parameters (i.e., train and pulse duration), was observed, with the highest variance concerning the purpose of seizure stimulation. The literature review highlighted an overall small sample size and minimal number of publications. Even though there is a rising trend towards stereotactic iEEG implantation, more data were available on subdural EEGs. CONCLUSION: This study shows individual and sparsely validated approach to CS in pediatric epilepsy. The literature review underscores the urgent need to harmonize pediatric intracranial EEG practices. More multicenter studies are needed to identify safe stimulation thresholds and allow implementation of evidence-based guidelines.
Keywords: mozková kůra; Seizures; elektrokortikografie; Child; Surveys and Questionnaires; Electrocorticography; Pediatrics; Kanada; Epilepsy; lidé; dítě; Brain Mapping; mapování mozku; Electroencephalography; Canada; Cerebral Cortex; Humans; záchvaty; pediatrie; elektroencefalografie; epilepsie; průzkumy a dotazníky